(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Entomological survey of mosquito vectors was carried out to determine species abundance and identify those responsible for the transmission of lymphatic filariasis in Talatan-mafara and Tsafe Local Government Areas of Zamfara State, Nigeria. Houses were randomly selected for mosquito collection. Aerosol (Baygon) was sprayed in the rooms to knockdown indoor resting mosquitoes. A total of 5,230 mosquitoes comprising of 3,104 females and 2,126 males were collected and 1,182 engorged females were dissected to isolate filarial worm, Wuchereria bancrofti. The species of mosquitoes encountered include Culex quinquefasciatus (84%), Anopheles funestus (10%) and Anopheles gambiae sl. (6%). The overall infection and infectivity rates of the mosquitoes with Wuchereria bancrofti were 1.86% and 1.44% respectively. The infection/infectivity rates of Culex quinquefasciatus, Anopheles funestus and Anopheles gambiae sl. were 1.01%/0.51%, 2.97%/2.97% and 4.54%/4.14% respectively.